During a visit of Van Ammers in Indonesia. Second of the left: Van Ammers, left, Maartense. Right: Bambang Subono and Bambang Isri Nugroho (1999)
During a visit of Van Ammers in Indonesia. Second of the left: Van Ammers, left, Maartense. Right: Bambang Subono and Bambang Isri Nugroho.